2004
DOI: 10.1063/1.1769099
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the deposition time of barrier layers on optical and structural properties of high-efficiency green-light-emitting InGaN∕GaN multiple quantum wells

Abstract: We reported the effect of the deposition time of barrier layers on optical and structural properties of high-efficiency green-light-emitting InGaN∕GaN multiple quantum wells (MQWs) by photoluminescence (PL) and high-resolution x-ray diffraction techniques. The MQW samples on (0001)-plane sapphire substrates were prepared with a ramping method by metalorganic chemical deposition. It was found that the structural or interface quality of the MQW system improved as the deposition time of barrier layers increased f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…3(a). The temperature-dependent PL intensity can be well fitted using the following Arrhenius formula3243444546: where I(T) represents the normalized integrated PL intensity. The parameters C 1 and C 2 are two constants related to the density of non-radiative recombination centres in the samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3(a). The temperature-dependent PL intensity can be well fitted using the following Arrhenius formula3243444546: where I(T) represents the normalized integrated PL intensity. The parameters C 1 and C 2 are two constants related to the density of non-radiative recombination centres in the samples.…”
Section: Resultsmentioning
confidence: 99%
“…The parameters C 1 and C 2 are two constants related to the density of non-radiative recombination centres in the samples. E A1 and E A2 are the activation energies corresponding to the non-radiative recombination process45464748. k B is Boltzmann's constant.…”
Section: Resultsmentioning
confidence: 99%
“…It is presumed that a slight increase in E H in sample C is related to the formation of stacking faults and the bending of lattice fringes due to increased misfit strain. On the other hand, it has been reported that E L values in the low temperature range are dominated by the degree of carrier localization captured in the potential minima [26]. Sample A with a very thin well-width, had a much larger activation energy than thermal energy kT when T was 80 K ($7 meV).…”
Section: Article In Pressmentioning
confidence: 97%
“…In particular, the integrated PL intensity of sample A decreased less rapidly in the temperature range 50-100 K. To achieve best-fit, we applied PL results to Eq. (1) using two activation energies [26], E L and E H , corresponding to two different nonradiative-recombination mechanisms at low and high temperature ranges, respectively.…”
Section: Article In Pressmentioning
confidence: 99%
“…Currently, the main issue related to the LEDs fabrication is to realize the white color emitters based on high-brightness blue and ultraviolet LEDs through improvements in the emission efficiency of visible LEDs [2]. For it, we have to reduce the dislocation density in nitride films and improve the electrical properties of the p-type contact layer doped with commonly used Mg atoms [3].…”
Section: Introductionmentioning
confidence: 99%